2006
DOI: 10.1002/rcm.2755
|View full text |Cite
|
Sign up to set email alerts
|

A general approach for the quantitative analysis of bisphosphonates in human serum and urine by high‐performance liquid chromatography/tandem mass spectrometry

Abstract: Bisphosphonates are extremely hydrophilic and structurally similar to many endogenous phosphorylated compounds, making their selective extraction from serum or urine very challenging. Many bisphosphonates lack strong chromophores for sensitive UV or fluorescence detection. We report here the first general approach to enable sensitive and selective quantitation of N-containing bisphosphonates by liquid chromatography/tandem mass spectrometry (LC/MS/MS) following derivatization with diazomethane. The novelty of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 26 publications
1
42
0
Order By: Relevance
“…Di-and triesters resulted mainly from the derivatization of clodronate, as shown in figure 12; further optimisation is needed to increase the yield of one of the derivatives in order to use this approach for quantitative purposes. Zhu et al (2006) reported a methodology for the quantification of risedronate and alendronate by LC-MS/MS in biological samples after derivatization of the phosphonate groups with diazomethane. As a general approach, the urine or serum samples were loaded onto Bond-Elut SAX solid-phase extraction (SPE) columns that were washed with water prior to on-column derivatization with diazomethane.…”
Section: Overview On Mass Spectrometric Analysis Of Biphosphonatesmentioning
confidence: 99%
“…Di-and triesters resulted mainly from the derivatization of clodronate, as shown in figure 12; further optimisation is needed to increase the yield of one of the derivatives in order to use this approach for quantitative purposes. Zhu et al (2006) reported a methodology for the quantification of risedronate and alendronate by LC-MS/MS in biological samples after derivatization of the phosphonate groups with diazomethane. As a general approach, the urine or serum samples were loaded onto Bond-Elut SAX solid-phase extraction (SPE) columns that were washed with water prior to on-column derivatization with diazomethane.…”
Section: Overview On Mass Spectrometric Analysis Of Biphosphonatesmentioning
confidence: 99%
“…Therefore, with recent improvement in the sensitivity of alendronate analytical assay, several research studies have attempted to optimize analysis of alendronate from plasma samples. A number of methods for the determination of alendronate in biological fluids have been published (Tsai et al, 1992;Usui et al, 1992Usui et al, , 1994Niemi et al, 1997;Sparidans and den Hartigh, 1999;Mönkkönen et al, 2000;Zhu et al, 2006;Tarcomnicu et al, 2007). Among these methods, high-performance liquid chromatography (HPLC) is a conventional technique that is readily used to detect alendronate in biological fluids.…”
Section: Introductionmentioning
confidence: 99%
“…However, these methods contain complex sample pretreatment processes which result in relatively low extraction efficiency and consequently, a large volume sample is necessary to detect trace amounts of alendronate. Recently, a sensitive liquid chromatography coupled with tandem mass spectrometry (LC/MS/MS) method is described to measure alendronate with only 500 µL of plasma regardless of extraction method (Zhu et al, 2006). However, high throughput analysis of alendronate using LC/MS/MS has some problems due to low ionization efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Bisphosphonates have been analyzed in pharmaceutical forms [16,17] and human plasma [18,19] using UV spectrophotometry [20,21], RP-HPLC with UV detection [22,23], fluorimetric detection [24] ion chromatography [25], capillary electrophoresis [26,27], LC-MS [28] and LC-MS 2 [29].…”
Section: Introductionmentioning
confidence: 99%